2005
DOI: 10.1016/j.jtcvs.2005.06.049
|View full text |Cite
|
Sign up to set email alerts
|

Does lobectomy for lung cancer in patients with chronic obstructive pulmonary disease affect lung function? A multicenter national study

Abstract: Patients with mild to severe chronic obstructive pulmonary disease could have a better late preservation of pulmonary function after lobectomy than healthy patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(46 citation statements)
references
References 21 publications
3
34
1
8
Order By: Relevance
“…In contrast, the effect of surgery to resect the tumour might alter the prevalence of COPD. Studies examining lung function after lobectomy suggest that lung function is only mildly affected [23,24]. The results from our study are very similar to those from WIN et al [23], who in a similarly sized study reported pre-operative FEV1 of ,2 L, dropping on average 600 mL, compared with 400 mL in our study (table 3).…”
Section: Thoracic Oncology Rp Young Et Alsupporting
confidence: 90%
“…In contrast, the effect of surgery to resect the tumour might alter the prevalence of COPD. Studies examining lung function after lobectomy suggest that lung function is only mildly affected [23,24]. The results from our study are very similar to those from WIN et al [23], who in a similarly sized study reported pre-operative FEV1 of ,2 L, dropping on average 600 mL, compared with 400 mL in our study (table 3).…”
Section: Thoracic Oncology Rp Young Et Alsupporting
confidence: 90%
“…These results indicate that the postoperative percent-of-predicted D LCO exhibits greater recovery compared with FEV 1 , which is similar to the findings reported by Brunelli et al 10 This finding may be explained by pulmonary vascular and hemodynamic compensatory mechanisms. 16 Several authors have reported that the percent-of-predicted FEV 1 in COPD subjects was decreased to a lesser extent or even improved after surgical resection compared with the percent-of-predicted FEV 1 in non-COPD subjects, [17][18][19] and the difference was more prominent at the early phase (1-3 months) after surgery. 10,20 This might be attributed to the similar effect of lung volume reduction surgery for subjects with bullous emphysema.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has also been noted that the actual postoperative percentof-predicted D LCO in subjects with COPD shows a marked increase with improvement of the ventilation/perfusion ratio. [17][18][19] In the present study, the actual percent-of-predicted FEV 1 had a tendency to exceed the predicted postoperative value in subjects with COPD (1.13 times the predicted postoperative value) at 1 month after surgery (P ϭ .06), but these values did not increase thereafter; meanwhile, the actual percent-of-predicted D LCO in COPD subjects showed no improvement, reaching only 73.5% of the preoperative value (1.05 times the predicted postoperative value) at 1 y after surgery. This inconsistency with the previous results may be due to the small number of COPD subjects (n ϭ 7) in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, it is recommended that lung function be performed in early stage lung cancer in order to assess peri-operative risk and the impact of surgical resection on post-operative lung function and respiratory reserve [33,34]. Studies examining lung function after lobectomy suggest that lung function is only minimally affected [35]. In addition, in the prospective study by MANNINO et al [11], where lung function was performed at baseline and prior to lung cancer diagnosis, the prevalence of GOLD stage I+ COPD was 48% in incident lung cancer cases, which is comparable to that reported in studies where lung function was performed at the time of diagnosis [18][19][20].…”
Section: Demographic Variables and Genotypingmentioning
confidence: 99%